A new species of genus Nishada Moore, 1878 (Lepidoptera, Erebidae, Arctiinae) from India - Joshi, Rahul; Kirti, Jagbir S.; Singh, Navneet (Zootaxa, 2016)
Genus Nishada Moore (1878) was proposed as a monotypic genus, under subfamily Lithosiinae, family Lithosiidae (now Lithosiini), including only Nishada flabrifera Moore (1878) from Calcutta (now as Kolkata), India. The genus is distributed from China to India, Thailand, Malaysia and up to Australia. The Indian fauna of Nishada is reported from North-East Himalayas, West Bengal (Kolkata) and South India. Members of this genus are unmarked, yellow to brown with short and broad wings. Genus Nishada has been taxonomically dealt by many authors but awaits thorough revision. History: Hampson (1900) included a total of ten species: Nishada niveola Hampson, 1900, Nishada syntomioides (Walker, 1862), Nishada impervia (Walker, 1865), Nishada marginalis (Felder 1875), Nishada tula Swinhoe, 1900, Nishada nodicornis (Walker 1862), Nishada rotundipennis (Walker 1862), Nishada flabrifera Moore, 1878, Nishada sambara (Moore 1859) and Nishada xantholoma (Snellen 1879). Swinhoe (1902) and Hampson (1911) then described two new species, Nishada melanistis and Nishada brunneipennis, respectively, followed by Rothschild (1912, 1913) who described a further seven new species, Nishada brunnea, Nishada flavens, Nishada testacea, Nishada griseoflava, Nishada fuscofascia, Nishada louisiadensis and Nishada aurantiaca, bringing the total to 19 species. Strand (1922) catalogued only 13 of these species in Nishada, transferring N. brunnea and N. fuscofascia to genus Scoliacma Meyrick (1886); N. testacea, N.griseoflava and N. louisiadensis Rothschild to Eilema Hübner (1819) and synonymising N. flavens with N. sambara. Next, Matsumura (1927) described N. formosibia, followed by two more species, N. aureocincta Debauche, 1938 and N. benjaminea Roepke, 1946. Holloway (2001) synonymised N. nodicornis with N. rotundipennis and added the description of a new subspecies, Nishada chilomorpha adunca Holloway, 2001 from Borneo, indicating a distributional range as far as North East India. The nominotypical subspecies, N. c. chilomorpha was suggested to be restricted to its type locality of Java. Bucsek (2012) added Nishada cameronensis, Dubatolov & Bucsek (2013) described Nishada schintlmeisteri and Bucsek (2016) described Nishada temenggora. So, at present, Nishada comprises19 species, of which three are known from India (Singh et al. 2014). Herein, we describe one further species, Nishada pseudochilomorpha Joshi & Singh sp. nov., from Jatinga (Assam, India). In addition, new distributional records are reported for N. flabrifera.